(untitled) (Baghdad Science Journal, 2021)
Global warming has had considerable effects on vital ecosystems, which has also been caused by increased temperatures and CO2 that follow changes in different abiotic factors, which poses threats to mangrove forests environment. This research was conducted to examine the physiological and morphological characteristics of the Rhizophora apiculata mangrove regarding higher air temperature for the variety of tree species that respond to climate change. Seedlings were cultivated for three months in regulated growth chambers with three varying temperatures of 38°C, 21°C under CO2 at 450 ppm, and ambient CO2 concentration i.e., 450 ± 20 ppm under average temperature at 28°C as the control condition. The plants were treated every 48 hours with 3 L of saline water of 28 ppt. After two weeks at high temperature, the mangrove showed positive results for all parameters. The temperature variations resulted in major variations, such as negative for increased temperature resulting in extreme damage to many samples while positive for decreased temperature resulting in slow development. The physiological results show decreased photosynthesis rates compared to controlled samples. These findings indicate that low photosynthetic capability levels could have occurred due to reduced CO2 fixative reaction mechanism, photosynthetic pigment material, and the discrepancy between respiratory and photosynthesis rate.